Effect of reaction conditions on the synthesis of cyclodextrin (CD) by using immobilized enzyme - Suhaily, Suhaimi; Rohaida, Che Man; Natassha, Jamil; Zatul Iffah, Mohd Arshad; Shalyda, Md Shaarani; Siti Zubaidah, Sulaiman; Siti Kholijah, Abdul Mudalip; Aizi Nor Mazila, Ramli (Penerbit Universiti Teknologi Malaysia, 2018)
The production of cyclodextrin (CD) over the years has been increasing due to the numerous applications in industries such as in food, cosmetic, pharmaceutical and agricultural industries. However, cyclodextrin glucanotransferase (CGTase) which involved in the enzymatic reaction on the production of CD is unstable and easily denatured at extreme conditions resulted in low CD production. Hence, the enzyme immobilization technique is introduced to overcome these problems and subsequently increase the production of CD. In the present study, the CGTase was immobilized on hollow fiber membrane to increase the production of CD during the reaction. The effect of reaction conditions (types of starch, concentration of starch, temperature and pH) of the immobilized enzyme on the production of CD were investigated. Among the three types of starch tested, the soluble potato starch was the most suitable substrate for the production of CD with 4.13 mg/mL. In addition, by using 3% (w/v) of the soluble potato starch, the production of CD was 5.22 mg/mL . The optimal reaction temperature and pH were found to be at 40°C and pH 6 with 5.21 mg/mL and 4.62 mg/ml of CD, respectively. The immobilized enzyme exhibited a 1.3-3-fold increase in CD production compared to the free enzyme. Therefore, the hollow fiber membrane is suitable to be used as a support for enzyme immobilization with the high production of CD.